Akuntabilitas Pertanggungjawaban Keuangan Desa Tantangan dan Strategi Peningkatan Tata Kelola - Maman Saepulloh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Accountability in village financial management is a crucial element in realizing good village governance and clean governance. As the transfer of village funds from the central government increases, there is a growing need for financial management and reporting mechanisms that are effective, efficient, transparent, honest, participatory, and accountable. This article aims to analyze the level of accountability in village financial management, identify key challenges in its implementation, and formulate improvement strategies. This study employs a descriptive qualitative approach with a literature review as the basis of analysis. The findings indicate that weak capacity and capability of village officials, low community participation, and limited oversight from supervisory institutions are the main obstacles to achieving village financial accountability. Therefore, improving human resource competencies, implementing digital-based reporting systems, and strengthening the role of the Village Consultative Body (BPD) are strategic recommendations to enhance transparency and accountability in village financial management.